Організація контролю експортних та імпортних операцій - Сидіч М.Ю. (Управління економікою: теорія та практика, 2024)
Стаття комплексно аналізує контроль експортних та імпортних операцій в Україні, зосереджуючись на законодавстві та механізмах митного нагляду. Досліджено сучасні тенденції та вплив міжнародних вимог на контроль зовнішньої торгівлі, виявлено ключові виклики щодо балансу спрощення процедур та ефективного нагляду. Проаналізовано митні ризики (контрабанда, фінансові злочини, ухилення від платежів) та шляхи їх зменшення для гармонізації торгівлі. Розглянуто роль автоматизованих систем аналізу ризиків (АСАУР) у оптимізації митних процедур та зниженні корупції. Підкреслено важливість міжнародної співпраці та обміну інформацією для ефективного контролю та дотримання принципів міжнародної торгівлі. Розглянуто спрощення митного адміністрування для легального бізнесу через цифровізацію. Обґрунтовано необхідність удосконалення митної політики України відповідно до вимог ВМО та ВТО, а також посилення координації між державними органами контролю ЗЕД. This article provides a comprehensive analysis of the organization of export and import operations control in Ukraine, with an emphasis on the regulatory framework and key mechanisms of customs supervision. Modern trends in customs administration and the impact of international requirements on the transformation of approaches to the control of foreign trade flows are investigated. Key challenges facing the control of foreign economic activity are identified, in particular, the need to balance the simplification of customs procedures with effective supervision of the cross-border movement of goods and services. The risks associated with customs regulation, including the fight against smuggling, financial crimes, and evasion of customs payments, and ways to reduce them, which contributes to the harmonization of trade processes, increasing their transparency and efficiency in the context of global economic changes, are analyzed. The role of automated risk analysis systems (ARAS) in optimizing customs procedures, minimizing administrative barriers, and reducing corruption risks is investigated. The importance of international cooperation and information exchange between customs authorities of different countries for the effective control of foreign trade operations, reducing the risks of customs legislation violations, and ensuring compliance with the principles of international trade is highlighted. Mechanisms for simplifying customs administration for legitimate businesses through the introduction of innovative technologies and the digitalization of customs procedures, which contributes to increasing the competitiveness of national enterprises in the global market, are considered. The article substantiates the need to improve Ukraine’s customs policy in accordance with the requirements of international organizations such as the World Customs Organization (WCO) and the World Trade Organization (WTO), as well as to strengthen coordination between state bodies that supervise foreign economic activity.